2009
DOI: 10.1177/0022022109348576
|View full text |Cite
|
Sign up to set email alerts
|

The Cultural Socialization of Emotion Regulation During Infancy

Abstract: This article offers a conceptual framework for the study of the development of emotion regulation during infancy that synthesizes evolutionary theory with cultural psychology. Two prototypical environments are characterized: Western urban middle-class families and rural farmer families in non-Western societies. The adult psychologies that are adapted to these environments are oriented toward autonomy and relatedness, respectively. A combined methodological approach of quantitative and qualitative procedures de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
161
0
22

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(189 citation statements)
references
References 27 publications
6
161
0
22
Order By: Relevance
“…The few culture-informed studies that focused on parenting and children's emotions infer parental beliefs from observed behavior (e.g. Keller & Otto, 2009;Trommsdorff & Friedlmeier, 2010). One study, however, assessed cultural beliefs and observed cultural differences in caregivers' behavioral responses to children's emotions .…”
mentioning
confidence: 99%
“…The few culture-informed studies that focused on parenting and children's emotions infer parental beliefs from observed behavior (e.g. Keller & Otto, 2009;Trommsdorff & Friedlmeier, 2010). One study, however, assessed cultural beliefs and observed cultural differences in caregivers' behavioral responses to children's emotions .…”
mentioning
confidence: 99%
“…Within a vast range of knowledge, some trends appear to be pivotal to our discussion. A large researching stream is focused on parental socialization, including the identification of universal patterns, variations across cultural contexts and consequences to child development (Keller and Otto, 2009;Grusec, 2011). Inspired by Vigostsky"s foundational works, other set of inquiries addresses "social cognition" as the process of learning from others, including implicit and explicit "mentalizing" (Destrebecqz and Cleeremans, 2005;Gelman, 2009;Frith and Frith, 2012).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Narratives from those grown up apart from production activities do not include similar reflections on childhood socialization, although a systematic biographical account of "child-rearing practices" (Keller and Otto, 2009) and "socialization styles" (Pellerin, 2005) would implicate additional work with caregivers. Besides, it is important to stress that our research focused on a low-educated population, so results shall be different studying privileged classes" biographies.…”
Section: "I Already Remember the Traditional Songs Sung By Women Whilmentioning
confidence: 99%
“…For this reason, people learn to soothe the expression of intense emotions. Keller and Otto (2009) also analyzed the cultural determinants of emotion regulation and emotion expression in two different social groups (urban context in Berlim, and rural context in Cameroon) and found contrasting results. What they considered to be an urban Western group prototype emphasizes the expression of emotions in children, while in rural context in Cameroon it is desired that children be calm and do not express their emotions.…”
Section: Emotional Expressionmentioning
confidence: 99%